Phenotypic plasticity in Populus trichocarpa clones across environments in the Nordic–Baltic region. Issue 1 (2nd January 2022) - Rönnberg-Wästljung, Ann Christin; Adler, Anneli; Karacic, Almir; Liepins, Kaspars; Richards, Thomas J.; Ingvarsson, Pär K.; Weih, Martin
ABSTRACT : Transition towards a bio-based society requires large amounts of woody biomass to be converted into biofuels and biomaterials. Populus species are good candidates for growth in short rotations, but there is a lack of climate-adapted plant material suitable for growth at the high latitudes of the Nordic–Baltic region. Here we studied the growth and phenology traits in 63 Populus trichocarpa clones earlier preliminary selected for growth at northern latitudes, in three different field sites; i.e. in central Sweden, eastern and western Latvia. The material showed moderate broad sense heritabilities, with high values for phenology traits, indicating opportunities for selection. Genotype × environment (g × e) interaction was identified for all traits, but the phenotypic correlation between pairs of sites provided more detailed information indicating the strength of the g × e interaction. The between-clone variation in plasticity was high, and we identified some clones showing a high and stable performance across the three sites. These clones are of particular interest for the commercial deployment and future breeding of Populus material for the Nordic–Baltic region.